Found but not lost: a skeptical note on the document discovered in the temple under Josiah - Henige, David P. (The journal of Hebrew scriptures, 2007)
In this paper I look at the famous story of the finding of the “book of the law” in the temple during the reign of Josiah. Adopting a pragmatic/plausible approach and keeping in mind the biblical testimony about earlier circumstances in Judah, I argue that the story as we have it lacks inherent plausibility and should be rejected as an etiological invention, whether or not of the time. None of the various scenarios that could explain its disappearance can also serve to explain why it remained hidden for so long, only to be discovered at just the right moment to provide a willing Josiah with the justification to begin a cultic reform program.